2022
DOI: 10.1002/jbt.23207
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow‐derived mesenchymal stem cells alleviate paclitaxel‐induced mechanical allodynia in rats

Abstract: Anticancer drug paclitaxel (PTX) frequently causes painful peripheral neuropathy; however, no medication has been shown to be effective in the treatment of this debilitating side effect. We aimed to investigate the efficacy of two different doses of allogeneic bone marrow-derived mesenchymal stem cells (BM-MSCs) on PTX-induced mechanical allodynia and spinal cytokine levels and their localization to target tissues such as the spinal cord and sciatic nerve. After the development of mechanical allodynia with rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…Xiang et al also observed the secretion of anti-inflammatory and anti-fibrotic factors that effectively improved renal function and inhibited the harmful progression of DPN [ 216 ]. Within CIPN, the administration of MSCs reversed the pain in mice exposed to chemotherapeutic medications known to negatively affect mitochondrial function and increase oxidative stress [ 220 , 221 ]. After 24 days of MSC treatment, mitochondrial respiration was restored, attributed to the increased MSC and M2 macrophage expression of IL-10 signaling [ 221 ].…”
Section: Neurotrophic Support In Neuropathy Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Xiang et al also observed the secretion of anti-inflammatory and anti-fibrotic factors that effectively improved renal function and inhibited the harmful progression of DPN [ 216 ]. Within CIPN, the administration of MSCs reversed the pain in mice exposed to chemotherapeutic medications known to negatively affect mitochondrial function and increase oxidative stress [ 220 , 221 ]. After 24 days of MSC treatment, mitochondrial respiration was restored, attributed to the increased MSC and M2 macrophage expression of IL-10 signaling [ 221 ].…”
Section: Neurotrophic Support In Neuropathy Treatmentmentioning
confidence: 99%
“…After 24 days of MSC treatment, mitochondrial respiration was restored, attributed to the increased MSC and M2 macrophage expression of IL-10 signaling [ 221 ]. The limitations of the systemic administration of MSCs are still an issue, requiring an abundant amount of MSCs in the hope that they stay viable, successfully differentiate, and accurately treat the desired target site [ 220 , 224 ].…”
Section: Neurotrophic Support In Neuropathy Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, inflammatory cytokines, such as TNF-α and IL-1β, have been reported to influence MSC differentiation, potentially biasing MSCs towards a particular cell phenotype, such as astrocytes. High levels of these pro-inflammatory cytokines have been shown to inhibit neuronal differentiation while promoting the differentiation of MSCs into astrocytes [40,41]. On the other hand, anti-inflammatory cytokines, such as IL-4 and IL-10, have been reported to promote neuronal differentiation and inhibit glial differentiation of MSCs [42].…”
Section: Promoting Neuronal Regenerationmentioning
confidence: 99%
“…To date, intravenous injection remains the most commonly used, convenient, and easily applicable method in clinical practice. However, the therapeutic effect of MSCs via intravenous injection might be affected by the potentially depositing in lung [ 18 , 19 ], yet the limited evidence upon peripheral neuropathic pain treatment was inconsistent [ 20 , 21 ]. Therefore, further investigations are imperative to clarify the efficacy and the concomitant underlying mechanisms of MSC administration via intravenous intervention.…”
Section: Introductionmentioning
confidence: 99%